Convergence of private and public law in the modern legislation of the Russian Federation - S A Ivanova (RUDN Journal of Law, 2013)
Division of the right into branches is an exclusive gain of the Soviet doctrine. Any modern legal system didn't provide and doesn't provide such division. The private law in a general view is set of the legislatively-legal complexes regulating a civil turn. In this case it is a question of files of the legislation and the legal phenomena coordinated by it which basis we see in certificates.